Dacentrurine stegosaurs (Dinosauria): A new specimen of Miragaia longicollum from the Late Jurassic of Portugal resolves taxonomical validity and shows the occurrence of the clade in North America - Costa, Francisco (2019)
The stegosaur species Miragaia longicollum was erected based on a partial anterior skeleton from the Upper Jurassic of Portugal. Until then, almost all stegosaur specimens in Portugal and Spain had been identified as Dacentrurus armatus, the sister taxon of M. longicollum and only other member of the clade Dacentrurinae. The holotypes of the two species have little overlap, since the holotype of D. armatus is mostly a posterior skeleton, so the classification of other specimens to either species is unclear and the validity of M. longicollum has been questioned and debated. Here we describe a largely complete specimen of M. longicollum discovered in 1959 in Atouguia da Baleia, Peniche, Portugal, consisting of both anterior and posterior portions of the skeleton. Comparisons to the holotypes of dacentrurines and other stegosaurs shed light on the convoluted relationships of this group. We conclude that M. longicollum is valid and rather different from D. armatus, and provide a revised diagnosis of M. longicollum, as well as revised diagnoses for D. armatus, Dacentrurinae, and the first diagnosis of the genus Miragaia, granting stability to these taxa and allowing new considerations to be given on the classification of other Iberian stegosaurs. This new specimen is, to date, the most complete dinosaur described from Portugal and the most complete stegosaur described from Europe. Miragaia shared anatomical features that show a close affinity to Alcovasaurus longispinus, confirming this to be the first known dacentrurine stegosaur in America, coherent with the hypothesis of an ephemeral land bridge between North America and Iberia that allowed faunal exchange.